IMPLEMENTASI PERATURAN DAERAH JAWA TIMUR NOMOR 8 TAHUN 2018 TENTANG PENYELENGGARAAN TOLERANSI KEHIDUPAN BERMASYARAKAT DI KOTA SURABAYA - Michael Andrew (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2021)
Pluralism and diversity are the most beautiful gifts from God Almighty for the Republic of Indonesia.However, this does not mean that the existence of pluralism and diversity means that the Republic ofIndonesia lives in peace and harmony continuously. In various regions in Indonesia the potential forconflicts due to differences in pluralism and diversity also often occurs. This confirms that pluralismand diversity is a gift from God Almighty, it does not mean that it exists and is left alone. In fact,pluralism and diversity must be kept, maintained, and carried out continuously. One of the effortsmade by the East Java Provincial Government is to produce Regional Regulation Number 8 of2018 concerning Community Life Tolerance in Society. Hopefully with this regional regulation, allefforts to maintain tolerance and manage conflicts related to intolerance can be resolved as well.This is also a form of the state’s presence in maintaining pluralism and diversity so that in the eventof a conflict, civil society groups do not fight with other civil society groups but can be resolvedcompletely and fairly under this regional regulation.